REVERSE LOGISTICS: CASE STUDY OF A REMANUFACTURER COMPANY FIRE EXTINGUISHER - Ortiz, Érica; Campolina, Juliana Mendes; Moris, Virgínia Aparecida Silva; Silva, João Eduardo Azevedo Ramos da (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
Concerns about the environment have led the society to develop new procedures to properly allocate the products that have reached the end of its useful life. From the point of view of companies operating channels of reverse logistics it is important to ensure both business viability and environmental compliance. This article presents a single case study and exploratory with the purpose of comparing motivations and difficulties for the operation of the reverse channel remanufacturing with the literature, in the case of fire extinguishers. For this reason, technical visits and interviews were conducted in a company that recharges fire extinguishers in Sorocaba region. The results showed that, in accordance with the literature, the extinguishers remanufacturing process provides economic and strategic advantage due to the opportunity to carry out other services such as installation of fire preventing and fighting systems, works maintenance, monitoring of Firefighters Survey and fire brigades training. On the other hand, the researched company does not present the typical problems reported in the literature about the uncertainties regarding the collection of extinguishers, their quality and acquisition of carcasses.Therefore concludes that the company has a well-established reverse logistics operation.